Characterization and Etiopathogenic Approach of Pediatric Renal Biopsy Patients in a Colombian Medical Center from 2007-2017 - Mayerly Prada Rico; Carmen Inés Rodríguez Cuellar; Monica Fernandez Hernandez; Luz Stella González Chaparro; Olga Lucía Prado Agredo; Ricardo Gastelbondo Amaya (International Journal of Nephrology)
Introduction. Renal biopsy is the principal instrument to evaluate the diagnosis and prognosis of children with kidney disease. There are relatively few studies establishing epidemiology of its findings in the pediatric population. Methods. A descriptive study was conducted to describe characteristics of pediatric patients who had undergone a renal biopsy over the last 10 years in a national reference center, trying to accomplish an etiopathogenic approach of biopsy findings. Results. 241 patients were included. Most frequent indications were nephrotic syndrome (34.1%) and systemic disease with renal involvement (30.2%). The most prevalent biopsy diagnosis was glomerulonephritis (44%) and among these patients, glomerulonephritis mediated by immune complexes was the most frequent pathogenic type (90.5%). When the biopsy was indicated for proteinuria plus hematuria and systemic disease with renal involvement, the most frequent biopsy diagnosis was glomerulonephritis (60 and 85%, respectively). For isolated hematuria, the predominant biopsy diagnosis was inherited diseases of the glomerular basement membrane (70%) and for nephrotic syndrome, podocytopathy (82%). Glomerulonephritis was more frequent in patients older than 10 yrs (65%) and the rate of postbiopsy major complications was low (1.2%). Conclusion. Immune complex glomerulonephritis was the most frequent histological finding, differing from previous reports. To our knowledge this is the first description that classifies biopsy findings according to the probable pathogenic mechanism.